XRF data for project 'Påvebullasigill från Roma (Papal seal from Roma, Gotland)', RAÄ-2023-0589 - Canosa, Elyse; Sandström, Tom; Widerström, Per; Östergren, Majvor (Swedish National Heritage Board, 2024)
X-ray fluorescence data from the project 'Påvebullasigill från Roma (Papal seal from Roma, Gotland)' (Diarienummer RAÄ-2023-0589), including files for sample descriptions. The instrument report which compiles the data is also included. The intention of the project was to determine if two pieces of lead papal seals found at an archaeological site in Roma, Gotland are from the same seal or two separate seals. XRF analysis was used to determine the elemental composition of both pieces (S1 and S2, Instrument report 1) as well as compare them to other lead objects found at the same site (Instrument report 2). A final analysis report is also included.
Keywords: Heritage Science; RAÄ-2023-0589; Gotlands Museum; Papal seals; Archaeology; X-ray fluorescence; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi